(untitled) (Victoria Journal of Management, 2025)
Green banking has emerged as a strategic move to align financial services with sustainability and long-term economic development. This systematic literature review analyses the impact of green banking practices on sustainable development based on 52 peer-reviewed articles from 2014 to 2025, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The study brings forth salient themes like green finance, institutional support, bank characteristics, stakeholder involvement, and barriers to adoption. Evidence shows that green banking activities, including green lending, paperless banking, and clean technology investments, not only contribute to environmental performance but also to long term profitability and customer confidence. Green finance acts as an effective mediator between banking operations and material sustainability results. Institutional and regulatory settings, bank size, and strategic readiness play significant roles in the successful operation of green banking. Adoption is nevertheless unbalanced, particularly for developing countries, due to market barriers such as low awareness, policy inconsistency, cost, and perceived complexity. Most of the studies included in this review employ quantitative research methods, primarily regression and structural equation modeling, with limited qualitative results. More context-specific and interdisciplinary research is therefore called for. The review highlights that green banking is not merely a corporate social responsibility program, but also a forward thinking financial approach aligned with international standards, such as the Paris Agreement and the United Nations Sustainable Development Goals. This convergence, in turn, contributes to the literature within academia and policy through contextual mapping of research gaps and outlining a premise for future studies aimed at mainstreaming sustainability in banking.